The effect of self-management practices and the work environment on employee job satisfaction (Case study of PT. Indi Platform Raksasa) - Sirait, Danni Rizki; Tarmidi, Didi (Technium Social Sciences Journal, 2021)
This research aims to determine how the description of self-management practices, work environment, and employee job satisfaction, as well as to determine how the influence of self-management practices and work environment on employee job satisfaction PT. Indi Platform Raksasa. The factors tested in the study were self-management practices and the work environment as independent variables, while job satisfaction was dependent variables. The research methods used in this research are descriptive and verification methods. The population in this study were employees at PT. Indi Platform Raksasa. The sampling technique used in this study was Purposive Sampling and the size of the sample in this study was calculated with the formula Slovin, so the total number was 144 respondents. The analytical methods used in this study are some linear regression analyses using SPSS25 for Windows. The results of this study show that self-management practices and work environments have an effect on employee job satisfaction at PT. Indi Platform Raksasa. The magnitude of the influence of self-management practices and the work environment on employee job satisfaction was 63.6%.